2020
DOI: 10.1155/2020/4289043
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Studies of Cement Production Processes

Abstract: The cement industry is one of the most intensive energy consumers in the industrial sectors. The energy consumption represents 40% to 60% of production cost. Additionally, the cement industry contributes around 5% to 8% of all man-made CO2 emissions. Physiochemical and thermochemical reactions involved in cement kilns are still not well understood because of their complexity. The reactions have a decisive influence on energy consumption, environmental degradation, and the cost of cement production. There are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 35 publications
(50 reference statements)
0
12
0
1
Order By: Relevance
“…Energy consumption in the Industrial sector ranges from 30-70% of the total energy used in some selected countries as previously reported by [1]. The cement sub-sector utilizes nearly 12-15% of entire industrial energy usage [1,2] due to the high temperatures required in the kilns. Cement is a vital product used in society for constructing modern infrastructure as well as safe and comfortable buildings.…”
Section: Introductionmentioning
confidence: 75%
“…Energy consumption in the Industrial sector ranges from 30-70% of the total energy used in some selected countries as previously reported by [1]. The cement sub-sector utilizes nearly 12-15% of entire industrial energy usage [1,2] due to the high temperatures required in the kilns. Cement is a vital product used in society for constructing modern infrastructure as well as safe and comfortable buildings.…”
Section: Introductionmentioning
confidence: 75%
“…This process is known as calcination and is treated in the literature as a two-step process that corresponds to endothermic reactions. The technical literature [1] reported that the first stage starts at around 80 o C and extends to a temperature in the order of 160 o C.…”
Section: Zone 3 Zone Formed By the Gypsum Bedmentioning
confidence: 99%
“…Gypsum is obtained from the chemical dehydration process of gypsum, which occurs between 80 °C and 160 °C, called calcination, and, usually, for this purpose, it uses rotary kilns [1]. Preferably, when fuels are used that, when burned, generate particulates, they use indirect burning furnaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concrete sector faces many problems to meet the high demand for OPC due to restricted reserves of limestone, slow production growth, and increasing carbon taxes. OPC is considered one of the predominant building materials investigated in the construction industry and reported as 4.2 billion tons (short scale) production in 2019 [ 3 ]. During the manufacturing of OPC, numerous gases affect the environment in series of ways [ 4 ].…”
Section: Introductionmentioning
confidence: 99%